Corporate Governance and Sustainability Performance: Analysis of Triple Bottom Line Performance - Hussain, Nazim; Rigoni, Ugo; Orij, René P. (Journal of business ethics, 2018)
The study empirically investigates the relationship between corporate governance and the triple bottom line sustainability performance through the lens of agency theory and stakeholder theory. We claim, in fact, that no single theory fully accounts for all the hypothesised relationships. We measure sustainability performance through manual content analysis on sustainability reports of the US-based companies. The study extends the existing literature by investigating the impact of selected corporate governance mechanisms on each dimension of sustainability performance, as defined by the GRI framework. Our approach allows to identify which governance mechanisms foster triple bottom line performance, also revealing that some mechanisms fit only specific dimension(s) of sustainability. The fact-based findings provide support for a new beginning in the theorising process in which the theories must try not only to provide rationale for the impact of corporate governance on sustainability, but also to explain which dimension of sustainability might be more affected. The most important implication for practitioners is the support for sustainability practices, which may be gained through implementation of particular corporate governance mechanisms. The findings contribute also to the improvement of the ongoing standard setting process, in particular as it concerns the in-depth revision of the economic dimension of sustainability carried out under the new GRI framework.